Risiko Paparan Formaldehida dari Beberapa Jenis Ikan pada Masyarakat di Kecamatan Dramaga, Bogor, Jawa Barat - Alfin Maulana Wihardi; Puspo Edi Giriwono; Dias Indrasti (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2023)
Residual formaldehyde compounds may be found in fish either naturally or intentionally added. Exposure of formaldehyde from food can cause damage to the gastrointestinal tract, liver, kidney, and is carcinogenic in humans. This study aims to estimate the risk value of formaldehyde exposure level due to fish consumption in the community population in Dramaga Subdistrict with deterministic approach. Fish consumption data was obtained from a consumption survey using a semi food frequency questionnaire (FFQ). The fish consumption survey was conducted on 505 respondents with an age range of 5-60 years and over. Formaldehyde analysis was conducted on four types of fish that are popular and often consumed by the community, namely salted peda fish, salted anchovy rice fish, salted japuh fish, and fresh anchovy fish. The results showed that formaldehyde levels in four types of fish range from 8.30 – 105.09 mg/kg. The average daily consumption of salted peda, salted anchovy rice, salted japuh, and fresh anchovy was 11.58±8.32; 8.85±4.93; 7.72±4.51; and 9.85±6.45 (g/day). The average daily exposure values of formaldehyde in salted peda, salted anchovy rice, salted japuh, and fresh anchovy were 0.0025; 0.0088; 0.0146; and 0.0014 (mg/kg bw/day). The overall of daily exposure value is still below the maximum oral exposure limit of 0.2 (mg/kg bb/day). The value of exposure risk with hazard quotient (HQ) in four types of fish is 0.007–0.073. The HQ was found to be below 1, indicating risk level of exposure to formaldehyde in the community in Dramaga Subdistrict is still within safe limits.